2012
DOI: 10.1515/1554-8597.1254
|View full text |Cite
|
Sign up to set email alerts
|

Youth Unemployment, Terrorism and Political Violence, Evidence from the Israeli/Palestinian Conflict

Abstract: This paper analyzes the relationship between youth unemployment and Palestinian violence. First a qualitative explanation of the underlying mechanism is given. Eventually, empirical results suggest that there is a positive association between the growth rate of youth unemployment and the brutality and incidence of violence, proxied by the numbers of victims, and incidents. Results also show that: (i) there is a negative association between the added value in the agricultural sector and both measures of violenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Caruso and Gavrilova (2012) focus on the connection between fluctuations in unemployment of young Palestinians and the observed level of violence extending the work on this topic of Benmelech et al (2012). The results in Caruso and Gavrilova (2012) show that there is a strong positive correlation between youth unemployment and Palestinian violence. They also provide an explanation of possible mechanisms behind this relationship and explore, in detail, this correlation across industries.…”
Section: Articles In This Special Issuementioning
confidence: 77%
See 1 more Smart Citation
“…Caruso and Gavrilova (2012) focus on the connection between fluctuations in unemployment of young Palestinians and the observed level of violence extending the work on this topic of Benmelech et al (2012). The results in Caruso and Gavrilova (2012) show that there is a strong positive correlation between youth unemployment and Palestinian violence. They also provide an explanation of possible mechanisms behind this relationship and explore, in detail, this correlation across industries.…”
Section: Articles In This Special Issuementioning
confidence: 77%
“…[e.g., Karol and Miguel (2007) and Gould and Klor (2012) [Lyall (2009[Lyall ( , 2010] and on Asian and African countries [e.g., Caruso and Schneider (2012)] just to name a few conflicts and a selected number of a long list of very interesting research projects. Klor (2006 and and Gould and Klor (2010) perform empirical analyses of the effect of terrorism on political attitudes of representative samples of the Israeli population using different data sets and methodologies.…”
Section: Political Effectiveness Of Terror Campaignsmentioning
confidence: 99%
“…A research by Caruso and Gavrilova analysed the relationship between unemployment and Violence in Pakistan. The findings indicated that most of the violence was stemming from the fact that many youths in that country were unemployed (Caruso & Gavrilova, 2012). The study in Pakistan appears to be one that can be compared largely to the Zambian environment where traces of political violence have been evident in every election in the last ten (10) years and involving the youth (Oliver, 2016).…”
Section: The Challenges Of Youth Unemploymentmentioning
confidence: 97%
“…In 2004 unemployment levels reached 23%, whereas the poverty level rose substantially, with 47% of Palestinians living below the official poverty line of 2.1 USD per day as estimated by The World Bank (2004). In turn, there is a positive association between the growth rate of youth unemployment and the brutality and incidence of violence (Caruso and Gavrilova 2012;Sayre 2009).…”
Section: The Closure Strategy To Control the Palestinian Territorymentioning
confidence: 99%